Police Science 2019
DOI: 10.4018/978-1-5225-7672-3.ch011
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Management Information System Support Rectifying First Responder Role Abandonment During Extreme Events

Abstract: Role abandonment once was considered unlikely by research scientists; however emergency management officials have experienced catastrophic events that counter prior assumptions. Event types such as deluges and pandemics surface as scenarios supporting one set of examples. The authors explore a different angle, focusing on individual practitioners including: (1) fire, (2) police and (3) emergency medical services. Surveys were taken by the various practitioner group types. Results suggested that there may be ro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(9 citation statements)
references
References 4 publications
0
9
0
Order By: Relevance
“…A willingness to work study found that healthcare workers were more willing to respond to mass casualty events (85.7%) as opposed to smallpox (61.1%) or SARS (48.4%). These results were repeated in several different studies and found willingness to work around 64% for an outbreak like smallpox (Markenson & Reilly, 2009; Noble et al, 2019). Across perception studies, there is a consistent difference between willingness to work during an outbreak as opposed to a natural disaster.…”
Section: Literature Reviewmentioning
confidence: 74%
See 4 more Smart Citations
“…A willingness to work study found that healthcare workers were more willing to respond to mass casualty events (85.7%) as opposed to smallpox (61.1%) or SARS (48.4%). These results were repeated in several different studies and found willingness to work around 64% for an outbreak like smallpox (Markenson & Reilly, 2009; Noble et al, 2019). Across perception studies, there is a consistent difference between willingness to work during an outbreak as opposed to a natural disaster.…”
Section: Literature Reviewmentioning
confidence: 74%
“…It is important to emphasize that PhotoVoice is a rarely used qualitative data collection method in public administration; yet, it was instrumental for the team to capture perishable data, including participant-driven recommendations, at a time when public safety agencies were facing unprecedented challenges. Additionally, most studies on role abandonment are limited in scope relying on a series of hypothetical scenarios (see Noble et al, 2019). This study utilized survey data on role abandonment and turnover intentions during an ongoing pandemic, providing opportunities to assess actual intentions instead of hypothetical versions which can produce an inflated sense of risk (Trainor & Barsky, 2011).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations